How, when and where? A systematic review on abortion decision making in legally restricted settings in sub-Saharan Africa, Latin America, and the Caribbean - Laura Hinson; Anam M. Bhatti; Meroji Sebany; Suzanne O. Bell; Mara Steinhaus; Claire Twose; Chimaraoke Izugbara (BMC, 2022)
Abstract Background With increasing global availability of medication abortion drugs, a safer option exists for many women to terminate a pregnancy even in legally restrictive settings. However, more than 22,000 women die each year from unsafe abortion, most often in developing countries where abortion is highly legally restricted. We conducted a systematic review to compile existing evidence regarding factors that influence women's abortion-related decision making in countries where abortion is highly legally restricted. Methods We searched ten databases in two languages (English and Spanish) for relevant literature published between 2000 and 2019 that address women's decision-making regarding when, where and how to terminate a pregnancy in sub-Saharan African, Latin American and the Caribbean countries where abortion is highly legally restricted. Results We identified 46 articles that met the review's inclusion criteria. We found four primary factors that influenced women's abortion-related decision-making processes: (1) the role of knowledge, including of laws, methods and sources; (2) the role of safety, including medical, legal and social safety; (3) the role of social networks and the internet, and; (4) cost affordability and convenience. Conclusions The choices women make after deciding to terminate a pregnancy are shaped by myriad factors, particularly in contexts where abortion is highly legally restricted. Our review catalogued the predominant influences on these decisions of when, where and how to abort. More research is needed to better understand how these factors work in concert to best meet women's abortion needs to the full limit of the law and within a harm reduction framework for abortions outside of legal indications.